EFEKTIVITAS MINUM AIR PUTIH DENGAN BACAAN SURAT AL-FATIHAH UNTUK MENURUNKAN KANTUK DI DALAM KELAS - Zumailah (Living Sufism: Journal of Sufism and Psychotherapy, 2023)
This study aims to determine the effectiveness of drinking water with the recitation of surat al-fatihah to reduce sleepiness in the classroom. The method used is quasi experimental method with the design "pretest posttest control group design". The study population was students of Madrasah Diniyah Annuqayah Latee 1 Guluk-Guluk Sumenep East Java. The sample research amounted to 30 students, each group consisted of 15 students by using two instruments namely the Sleepiness Scale and the Sleepiness Module which was developed by the researcher. The conclusion of the results of this study are: (1) drinking water with the recitation of surat al-Fatihah is effective to reduce sleepiness in the classroom. The test results of- t pired sample t-test which has significance value of 0.000 (0,000< 0.05). Students who received the treatment obtained a higher mean decrease in sleepiness (48, 40) compared to before treatment (64, 73). (2) there is a significant difference in posttet between the drowsiness condition of the experimental group and the control group after the experimental group was treated, this is indicated by test results of -t independent sample t-test, which has a significance value of 0.000 (0.000 < P 0.05). Thus, it can be concluded that Ho is rejected and Hi is accepted. Based on the significance value, it can be concluded that the treatment of drinking water with the recitation of surat al-fatihah is effective to reduce sleepiness in the classroom of students of Madrasah Diniyah Annuqayah Latee 1 Guluk-Guluk Sumenep East Java.